MANAJEMEN AUDIT SUMBER DAYA MANUSIA UNTUK MENCAPAI PENINGKATAN KINERJA MANAJEMEN - Sumadji Harryono (Universitas Negeri Surabaya, 2018)
The purpose, was to determine and ensure that the programs / activities of HR was effective, economical, and efficient as well as ensuring compliance with various program / activity against the human resources laws, regulations and policies applicable in the company. Methods used include library research by studying books, scientific journals, and literature that is closely related to the subject matter of the thesis as well as field research by interviewing the relevant parts of the company's activities and observations, questionnaires and documents human resources related. Human resource audit is a systematic examination and assessment, objective and documented on the organizational functions that are affected by human resource (HR) management with the aim of ensuring the fulfillment of the principle of appropriateness, effectiveness and efficiency of refineries and human resources to support the achievement of functional goals and objectives of the organization as a whole better for the medium term, and long term objectives of this study is to determine how HR audits role in improving the effectiveness of employees.